Explaining subscription intention for video streaming platforms in China: Integrating the UTAUT2 model, perceived value theory, and S-O-R theory - Tong Wu; Nan Jiang; Saeed Pahlevan Sharif; Mobai Chen (PLoS ONE, 2025)
Purpose This study examines the factors influencing the intention to subscribe to video streaming platforms in China through integrating the extended unified theory of acceptance and use of technology (UTAUT2), perceived value theory, and stimulus–organism–response (S-O-R) theory. Design/methodology/approach A quantitative study was conducted to test the hypothesized relationships among the constructs using partial least squares structural equation modeling (PLS-SEM). The sample included 506 viewers of video streaming platforms. Findings The results showed that performance expectancy, effort expectancy, social influence, and hedonic motivation had a positive relationship with subscription intention in video streaming platforms. Additionally, perceived value mediated these relationships. Also, habit was positively related to subscription intention. Finally, the attractiveness of alternatives moderated the relationship between perceived value and subscription intention of video streaming platforms in China. Originality/value This study introduces a moderated mediation mechanism to explain the intention to subscribe to video streaming platforms in China, utilizing the UTAUT2 model, perceived value theory, and S-O-R theory.